Ultrafiltration membrane for deep water treatment and preparation method thereof
By blending block polysulfone particles and other materials in the ultrafiltration membrane to prepare the cast membrane liquid, the membrane pollution problem is solved, the hydrophilicity, permeability and anti-fouling properties of the ultrafiltration membrane are improved, and the service life is extended.
Patent Information
- Application Number
- CN202510315011.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-18
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2045-03-18
AI Technical Summary
Existing ultrafiltration membranes face membrane pollution problems when dealing with domestic sewage, which affects their selectivity, permeability and service life.
Block polysulfone particles, polyvinylpyrrolidone, sulfonated Ag-MOF, quaternized cellulose nanocrystals and N-methylpyrrolidone were used to blend to obtain a cast membrane liquid, and an ultrafiltration membrane was prepared by scraping membrane technology.
It improves the hydrophilicity and porosity of the ultrafiltration membrane, improves permeability and anti-fouling properties, and extends the service life.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of ultrafiltration membranes, in particular to an ultrafiltration membrane for deep water treatment and a preparation method thereof. Background Art
[0002] With the acceleration of urbanization and the growth of population, the discharge of water treatment, especially sewage treatment, has gradually increased year by year. Although traditional sewage treatment processes, such as activated sludge method and oxidation ditch, can effectively remove most organic matter and suspended solids, their effluent quality is usually difficult to meet the increasingly stringent emission standards or the needs of water reuse. Residual pollutants in domestic sewage (such as colloids, pathogenic microorganisms, trace organic matter and some soluble pollutants) have become the key bottleneck restricting the improvement of water quality. In such an environment, deep treatment technology has gradually become a hot spot for research and application, and ultrafiltration membranes use a pore size range of 1-100 nm to remove suspended solids, colloids, bacteria and macromolecular organic matter in water through physical interception. Due to its high-efficiency separation performance, it has become one of the core means in the field of deep treatment.
[0003] However, in domestic sewage treatment, although ultrafiltration membrane technology is highly efficient, it still faces multiple challenges. Among them, membrane fouling seriously affects the selectivity, permeability and service life of ultrafiltration membranes. Therefore, finding ultrafiltration membrane materials with more optimized performance is still a key issue in membrane applications. Summary of the invention
[0004] The object of the present invention is to provide an ultrafiltration membrane for deep water treatment and a preparation method thereof, so as to solve the problems raised in the prior art.
[0005] To achieve the above object, the present invention provides the following technical solutions: A method for preparing an ultrafiltration membrane for deep water treatment comprises the following steps: Step 1: After drying and removing water from phenolphthalein, 4,4'-dichlorodiphenyl sulfone, anhydrous potassium carbonate and polyethylene glycol respectively, phenolphthalein, 4,4'-dichlorodiphenyl sulfone and anhydrous potassium carbonate are mixed, toluene and dimethylacetamide are added, and the mixture is heated to 140° C. and stirred for reaction for 6-10 hours until no water is taken out, and the mixture is heated to 160-180° C. to remove toluene, and the mixture is continued to react for 8 hours, and the mixture is cooled to 150° C., polyethylene glycol is added, and the mixture is continued to react for 1-2 hours, and the mixture is poured into pure water for sedimentation, and dilute hydrochloric acid is added dropwise, and the solid is filtered out and then crushed, and then washed and dried to obtain segmented polysulfone particles; Step 2: Mix the segmented polysulfone particles prepared in step 1 with polyvinyl pyrrolidone, sulfonated Ag-MOF, quaternized cellulose nanocrystals, and N-methylpyrrolidone, stir at 40-60°C for 6-8h, and then vacuum degas for 1h to obtain a casting solution; pour the casting solution onto a clean glass plate, use a scraper with a gap of 100-150μm to scrape it into a flat membrane, let it stand for 15-30s, immerse it in pure water until the primary membrane falls off, replace the pure water every 6-8h to obtain the final ultrafiltration membrane.
[0006] Wherein, the ultrafiltration membrane in step 2 comprises the following raw materials in parts by weight: 15-20 parts of segmented polysulfone particles, 3-5 parts of polyvinyl pyrrolidone, 2-5 parts of sulfonated Ag-MOF, 6-10 parts of quaternized cellulose nanocrystals and 70-80 parts of N-methylpyrrolidone.
[0007] In step 1, the usage ratio of phenolphthalein, 4,4'-dichlorodiphenyl sulfone and polyethylene glycol is 1 mol: 1 mol: 25-80 g.
[0008] The preparation steps of sulfonated Ag-MOF are as follows: dopamine hydrochloride is placed in a Tris buffer solution with a pH of 8.5, Ag-MOF is added and ultrasonicated for 10 minutes, the reaction is stirred for 4-6 hours, centrifuged, washed and dried, then transferred to pure water and ultrasonicated for 20 minutes, sodium 3-mercapto-1-propane sulfonate is added, the temperature is raised to 50-60°C, the reaction is stirred for 24 hours, centrifuged, washed and dried.
[0009] Preferably, the mass ratio of Ag-MOF to dopamine hydrochloride and sodium 3-mercapto-1-propane sulfonate is 1:1:(0.6-1.5).
[0010] The preparation steps of quaternized cellulose nanocrystals are as follows: Step s1: Take cellulose nanocrystals and place them in a nitric acid solution for oscillation activation for 6 hours, then freeze-dry them, mix them with sodium periodate, place them in pure water, stir and react for 3 hours, then add ethylene glycol, centrifuge and wash them with water, mix them with cysteine, heat them to 40°C under nitrogen protection and stir them for 5 hours to obtain thiolated cellulose nanocrystals for later use; Step s2: dissolving dimethylaminoethyl methacrylate in N,N'-dimethylformamide, adding dodecane bromide, stirring and reacting for 48 hours under a nitrogen atmosphere, adding anhydrous ether to repeat precipitation and purification to obtain a quaternary ammonium salt monomer for later use; Step s3: placing the thiolated cellulose nanocrystals prepared in step s1 in dimethyl sulfoxide, adding the quaternary ammonium salt monomer prepared in step s2 and 2,2-dihydroxymethylpropionic acid, introducing nitrogen, reacting under ultraviolet light for 10 hours, centrifugally washing and freeze-drying to obtain quaternary ammonium cellulose nanocrystals.
[0011] Preferably, in step s1, the mass ratio of cellulose nanocrystals to sodium periodate and cysteine is 1:(0.6-1):(1-2); and in step s2, the volume ratio of dimethylaminoethyl methacrylate to dodecane bromide is (4-5):6.
[0012] Preferably, in step s3, the mass ratio of the thiolated cellulose nanocrystals to the quaternary ammonium salt monomer is 1:1; the mass fraction of 2,2-dihydroxymethylpropionic acid is 1.5%-2% of the thiolated cellulose nanocrystals.
[0013] An ultrafiltration membrane for deep water treatment is prepared by the above preparation method.
[0014] Compared with the prior art, the present invention has the following beneficial effects: 1. The present invention uses block polysulfone particles and polyvinyl pyrrolidone, sulfonated Ag-MOF, quaternized cellulose nanocrystals, and N-methylpyrrolidone to mix to obtain a casting solution, and scrapes to obtain an ultrafiltration membrane; wherein the block polysulfone particles are obtained by co-condensation of phenolphthalein, 4,4'-dichlorodiphenyl sulfone, and polyethylene glycol, and the polyethylene glycol has good biocompatibility and hydrophilicity, effectively improves the hydrophilicity of the ultrafiltration membrane, and increases the porosity and permeability of the membrane; the sulfonated Ag-MOF uses a silver metal-organic framework, which has excellent antibacterial properties, and utilizes the mikrophore of polydopamine and thiol to obtain a membrane casting solution; By introducing sulfonic acid groups, hydrophilic groups, on the surface of Ag-MOF, the compatibility of Ag-MOF and ultrafiltration membrane is improved, the stability of Ag-MOF and membrane matrix is improved, the shedding is slowed down and the service life is increased; cellulose nanocrystals have good hydrophilicity and adsorption. By introducing thiol and quaternary ammonium salt monomers to produce click reactions, quaternization is achieved, the dispersibility and compatibility of CNC in ultrafiltration membrane are improved, and cellulose is created again. Use value, at the same time, quaternary ammonium salts are introduced to give the membrane surface good hydrophilicity, and improve the anti-fouling performance of ultrafiltration membrane during water treatment.
[0015] 2. The block polysulfone particles, sulfonated Ag-MOF and quaternized cellulose nanocrystals in the raw materials of the product of the present invention are self-developed products, and the product quality is effectively controlled during the production process. DETAILED DESCRIPTION
[0016] Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in the field without making any creative work shall fall within the scope of protection of the present invention.
[0017] In the experiment, the molecular weight of polyethylene glycol was 2000Da; polyvinyl pyrrolidone K30 and Ag-MOF were purchased from Xi'an Qiyue Biology with the product number of Q-0340346; phenolphthalein, 4,4'-dichlorodiphenyl sulfone, anhydrous potassium carbonate and polyethylene glycol all needed to be dried and dehydrated before being put into use; The preparation steps of sulfonated Ag-MOF are as follows: 1g dopamine hydrochloride is placed in 100mL pH 8.5, 10mM Tris buffer solution, 1g Ag-MOF is added, ultrasonicated for 10min, stirred for reaction for 4h, centrifuged, washed and dried, then transferred to pure water for ultrasonication for 20min, 1g sodium 3-mercapto-1-propane sulfonate is added, the temperature is raised to 50℃, stirred for reaction for 24h, centrifuged, washed and dried to obtain; Embodiment 1: Provide a method for preparing an ultrafiltration membrane for deep water treatment, the specific steps are as follows: Step 1: 9.547 g of phenolphthalein, 8.620 g of 4,4'-dichlorodiphenyl sulfone and 5.526 g of anhydrous potassium carbonate were mixed, and 20 mL of toluene and 100 g of dimethylacetamide were added, and the mixture was heated to 140° C. and stirred for 6 h until no water was taken out, and the mixture was heated to 160° C. to remove toluene, and the mixture was continued to react for 8 h, and the mixture was cooled to 150° C., 1.753 g of polyethylene glycol was added, and the mixture was continued to react for 2 h, and then the mixture was poured into pure water for sedimentation, and dilute hydrochloric acid was added dropwise until the pH was 1, and the solid was filtered out and crushed, and then washed and dried to obtain segmented polysulfone particles; Step 2: Mix 18 g of the segmented polysulfone particles prepared in step 1 with 3 g of polyvinyl pyrrolidone, 4 g of sulfonated Ag-MOF, 8 g of quaternized cellulose nanocrystals, and 72 g of N-methylpyrrolidone, stir at 40°C for 8 h, and then vacuum degas for 1 h to obtain a casting solution; pour the casting solution onto a clean glass plate, and use a scraper with a gap of 150 μm to scrape it into a flat membrane. After standing for 30 seconds, immerse it in pure water until the primary membrane falls off, and replace the pure water every 8 hours to obtain the final ultrafiltration membrane.
[0018] The preparation steps of quaternized cellulose nanocrystals are as follows: Step s1: 5 g of cellulose nanocrystals were placed in 100 mL of 0.5 mol / L nitric acid solution for oscillation activation for 6 h, then freeze-dried, mixed with 5 g of sodium periodate, placed in pure water, stirred for reaction for 3 h, added with 8 mL of ethylene glycol, centrifuged and washed with water, mixed with 5 g of cysteine, heated to 40° C. under nitrogen protection and stirred for 5 h to obtain thiolated cellulose nanocrystals for later use; Step s2: dissolving 10 mL of dimethylaminoethyl methacrylate in 25 mL of N,N'-dimethylformamide, adding 15 mL of dodecane bromide, stirring and reacting for 48 h under a nitrogen atmosphere, adding anhydrous ether to repeat precipitation and purification to obtain a quaternary ammonium salt monomer for later use; Step s3: 5 g of the thiolated cellulose nanocrystals prepared in step s1 are placed in 100 mL of dimethyl sulfoxide, 5 g of the quaternary ammonium salt monomer prepared in step s2 and 0.075 g of 2,2-dihydroxymethylpropionic acid are added, nitrogen is introduced, and the mixture is reacted under ultraviolet light for 10 h. The mixture is then centrifuged, washed, and freeze-dried to obtain quaternary cellulose nanocrystals.
[0019] Embodiment 2: Provide a method for preparing an ultrafiltration membrane for deep water treatment, the specific steps are as follows: Step 1: 9.548 g of phenolphthalein, 8.612 g of 4,4'-dichlorodiphenyl sulfone, and 5.525 g of anhydrous potassium carbonate were mixed, and 20 mL of toluene and 100 g of dimethylacetamide were added, and the mixture was heated to 140° C. and stirred for reaction for 6 h until no water was taken out, and the mixture was heated to 160° C. to remove toluene, and the reaction was continued for 8 h, and the mixture was cooled to 150° C., 0.844 g of polyethylene glycol was added, and the reaction was continued for 2 h, and the mixture was poured into pure water for sedimentation, and dilute hydrochloric acid was added dropwise until the pH was 1, and the solid was filtered out and crushed, and then washed and dried to obtain segmented polysulfone particles; Step 2: Mix 15 g of the segmented polysulfone particles prepared in step 1 with 3 g of polyvinyl pyrrolidone, 3 g of sulfonated Ag-MOF, 6 g of quaternized cellulose nanocrystals, and 78 g of N-methylpyrrolidone, stir at 40°C for 8 h, and then vacuum degas for 1 h to obtain a casting solution; pour the casting solution onto a clean glass plate, and use a scraper with a gap of 150 μm to scrape it into a flat membrane. After standing for 30 seconds, immerse it in pure water until the primary membrane falls off, and replace the pure water every 8 hours to obtain the final ultrafiltration membrane.
[0020] The preparation steps of quaternized cellulose nanocrystals are as follows: Step s1: 5 g of cellulose nanocrystals were placed in 100 mL of 0.5 mol / L nitric acid solution for oscillation activation for 6 h, then freeze-dried, mixed with 5 g of sodium periodate, placed in pure water, stirred for reaction for 3 h, added with 8 mL of ethylene glycol, centrifuged and washed with water, mixed with 5 g of cysteine, heated to 40° C. under nitrogen protection and stirred for 5 h to obtain thiolated cellulose nanocrystals for later use; Step s2: dissolving 10 mL of dimethylaminoethyl methacrylate in 25 mL of N,N'-dimethylformamide, adding 15 mL of dodecane bromide, stirring and reacting for 48 h under a nitrogen atmosphere, adding anhydrous ether to repeat precipitation and purification to obtain a quaternary ammonium salt monomer for later use; Step s3: 5 g of the thiolated cellulose nanocrystals prepared in step s1 are placed in 100 mL of dimethyl sulfoxide, 5 g of the quaternary ammonium salt monomer prepared in step s2 and 0.075 g of 2,2-dihydroxymethylpropionic acid are added, nitrogen is introduced, and the mixture is reacted under ultraviolet light for 10 h. The mixture is then centrifuged, washed, and freeze-dried to obtain quaternary cellulose nanocrystals.
[0021] Embodiment 3: Provide a method for preparing an ultrafiltration membrane for deep water treatment, the specific steps are as follows: Step 1: 9.549 g of phenolphthalein, 8.617 g of 4,4'-dichlorodiphenyl sulfone, and 5.529 g of anhydrous potassium carbonate were mixed, and 20 mL of toluene and 100 g of dimethylacetamide were added, and the mixture was heated to 140° C. and stirred for reaction for 6 h until no water was taken out, and the mixture was heated to 160° C. to remove toluene, and the reaction was continued for 8 h, and the mixture was cooled to 150° C., 2.398 g of polyethylene glycol was added, and the reaction was continued for 2 h, and the mixture was poured into pure water for sedimentation, and dilute hydrochloric acid was added dropwise until the pH was 1, and the solid was filtered out and crushed, and then washed and dried to obtain segmented polysulfone particles; Step 2: Mix 20 g of the segmented polysulfone particles prepared in step 1 with 5 g of polyvinyl pyrrolidone, 5 g of sulfonated Ag-MOF, 10 g of quaternized cellulose nanocrystals, and 80 g of N-methylpyrrolidone, stir at 40 °C for 8 h, and then vacuum degas for 1 h to obtain a casting solution; pour the casting solution onto a clean glass plate, and use a scraper with a gap of 150 μm to scrape it into a flat membrane. After standing for 30 seconds, immerse it in pure water until the primary membrane falls off, and replace the pure water every 8 hours to obtain the final ultrafiltration membrane.
[0022] The preparation steps of quaternized cellulose nanocrystals are as follows: Step s1: 5 g of cellulose nanocrystals were placed in 100 mL of 0.5 mol / L nitric acid solution for oscillation activation for 6 h, then freeze-dried, mixed with 5 g of sodium periodate, placed in pure water, stirred for reaction for 3 h, added with 8 mL of ethylene glycol, centrifuged and washed with water, mixed with 5 g of cysteine, heated to 40° C. under nitrogen protection and stirred for 5 h to obtain thiolated cellulose nanocrystals for later use; Step s2: dissolving 10 mL of dimethylaminoethyl methacrylate in 25 mL of N,N'-dimethylformamide, adding 15 mL of dodecane bromide, stirring and reacting for 48 h under a nitrogen atmosphere, adding anhydrous ether to repeat precipitation and purification to obtain a quaternary ammonium salt monomer for later use; Step s3: 5 g of the thiolated cellulose nanocrystals prepared in step s1 are placed in 100 mL of dimethyl sulfoxide, 5 g of the quaternary ammonium salt monomer prepared in step s2 and 0.075 g of 2,2-dihydroxymethylpropionic acid are added, nitrogen is introduced, and the mixture is reacted under ultraviolet light for 10 h. The mixture is then centrifuged, washed, and freeze-dried to obtain quaternary cellulose nanocrystals.
[0023] Comparative Example 1: As a control experiment of Example 1, the segmented polysulfone particles were not subjected to polyethylene glycol blocking, and the specific steps were as follows: Step 1: 9.544 g of phenolphthalein, 8.618 g of 4,4'-dichlorodiphenyl sulfone, and 5.528 g of anhydrous potassium carbonate were mixed, and 20 mL of toluene and 100 g of dimethylacetamide were added, and the mixture was heated to 140° C. and stirred for 6 h until no water was taken out, and the mixture was heated to 160° C. to remove toluene, and the mixture was reacted for 8 h, and the mixture was poured into pure water for sedimentation, and dilute hydrochloric acid was added dropwise until the pH was 1, and the solid was filtered out and crushed, and then washed and dried to obtain polysulfone particles; Step 2: Mix 18 g of the polysulfone particles prepared in step 1 with 3 g of polyvinyl pyrrolidone, 4 g of sulfonated Ag-MOF, 8 g of quaternized cellulose nanocrystals, and 72 g of N-methylpyrrolidone, stir at 40 °C for 8 h, and then vacuum degas for 1 h to obtain a casting solution; pour the casting solution onto a clean glass plate, and use a scraper with a gap of 150 μm to scrape it into a flat membrane. After standing for 30 seconds, immerse it in pure water until the primary membrane falls off, and replace the pure water every 8 hours to obtain the final ultrafiltration membrane.
[0024] The preparation steps of quaternized cellulose nanocrystals are as follows: Step s1: 5 g of cellulose nanocrystals were placed in 100 mL of 0.5 mol / L nitric acid solution for oscillation activation for 6 h, then freeze-dried, mixed with 5 g of sodium periodate, placed in pure water, stirred for reaction for 3 h, added with 8 mL of ethylene glycol, centrifuged and washed with water, mixed with 5 g of cysteine, heated to 40° C. under nitrogen protection and stirred for 5 h to obtain thiolated cellulose nanocrystals for later use; Step s2: dissolving 10 mL of dimethylaminoethyl methacrylate in 25 mL of N,N'-dimethylformamide, adding 15 mL of dodecane bromide, stirring and reacting for 48 h under a nitrogen atmosphere, adding anhydrous ether to repeat precipitation and purification to obtain a quaternary ammonium salt monomer for later use; Step s3: 5 g of the thiolated cellulose nanocrystals prepared in step s1 are placed in 100 mL of dimethyl sulfoxide, 5 g of the quaternary ammonium salt monomer prepared in step s2 and 0.075 g of 2,2-dihydroxymethylpropionic acid are added, nitrogen is introduced, and the mixture is reacted under ultraviolet light for 10 h. The mixture is then centrifuged, washed, and freeze-dried to obtain quaternary cellulose nanocrystals.
[0025] Comparative Example 2: As a control experiment of Example 1, no sulfonated Ag-MOF was added to the prepared ultrafiltration membrane, and the specific steps were as follows: Step 1: 9.55 g of phenolphthalein, 8.62 g of 4,4'-dichlorodiphenyl sulfone, and 5.53 g of anhydrous potassium carbonate were mixed, and 20 mL of toluene and 100 g of dimethylacetamide were added, and the mixture was heated to 140° C. and stirred for 6 h until no water was taken out, and the mixture was heated to 160° C. to remove toluene, and the mixture was continued to react for 8 h, and the mixture was cooled to 150° C., 1.75 g of polyethylene glycol was added, and the mixture was continued to react for 2 h, and then the mixture was poured into pure water for sedimentation, and dilute hydrochloric acid was added dropwise until the pH was 1, and the solid was filtered out and crushed, and then washed and dried to obtain segmented polysulfone particles; Step 2: Mix 18 g of the segmented polysulfone particles prepared in step 1, 3 g of polyvinyl pyrrolidone, 8 g of quaternized cellulose nanocrystals, and 72 g of N-methylpyrrolidone, stir at 40°C for 8 h, and then vacuum degas for 1 h to obtain a casting solution; pour the casting solution onto a clean glass plate, and use a scraper with a gap of 150 μm to scrape it into a flat membrane. After standing for 30 seconds, immerse it in pure water until the primary membrane falls off, and replace the pure water every 8 hours to obtain the final ultrafiltration membrane.
[0026] The preparation steps of quaternized cellulose nanocrystals are as follows: Step s1: 5 g of cellulose nanocrystals were placed in 100 mL of 0.5 mol / L nitric acid solution for oscillation activation for 6 h, then freeze-dried, mixed with 5 g of sodium periodate, placed in pure water, stirred for reaction for 3 h, added with 8 mL of ethylene glycol, centrifuged and washed with water, mixed with 5 g of cysteine, heated to 40° C. under nitrogen protection and stirred for 5 h to obtain thiolated cellulose nanocrystals for later use; Step s2: dissolving 10 mL of dimethylaminoethyl methacrylate in 25 mL of N,N'-dimethylformamide, adding 15 mL of dodecane bromide, stirring and reacting for 48 h under a nitrogen atmosphere, adding anhydrous ether to repeat precipitation and purification to obtain a quaternary ammonium salt monomer for later use; Step s3: 5 g of the thiolated cellulose nanocrystals prepared in step s1 are placed in 100 mL of dimethyl sulfoxide, 5 g of the quaternary ammonium salt monomer prepared in step s2 and 0.075 g of 2,2-dihydroxymethylpropionic acid are added, nitrogen is introduced, and the mixture is reacted under ultraviolet light for 10 h. The mixture is then centrifuged, washed, and freeze-dried to obtain quaternary cellulose nanocrystals.
[0027] Comparative Example 3: As a control experiment of Example 1, quaternary ammonium cellulose nanocrystals were not added to the prepared ultrafiltration membrane, and the specific steps were as follows: Step 1: 9.55 g of phenolphthalein, 8.62 g of 4,4'-dichlorodiphenyl sulfone, and 5.53 g of anhydrous potassium carbonate were mixed, and 20 mL of toluene and 100 g of dimethylacetamide were added, and the mixture was heated to 140° C. and stirred for 6 h until no water was taken out, and the mixture was heated to 160° C. to remove toluene, and the mixture was continued to react for 8 h, and the mixture was cooled to 150° C., 1.75 g of polyethylene glycol was added, and the mixture was continued to react for 2 h, and then the mixture was poured into pure water for sedimentation, and dilute hydrochloric acid was added dropwise until the pH was 1, and the solid was filtered out and crushed, and then washed and dried to obtain segmented polysulfone particles; Step 2: Mix 18 g of the segmented polysulfone particles prepared in step 1 with 3 g of polyvinyl pyrrolidone, 4 g of sulfonated Ag-MOF, and 72 g of N-methylpyrrolidone, stir at 40 °C for 8 h, and then vacuum degas for 1 h to obtain a casting solution; pour the casting solution onto a clean glass plate, and use a scraper with a gap of 150 μm to scrape it into a flat membrane. After standing for 30 seconds, immerse it in pure water until the primary membrane falls off, and replace the pure water every 8 hours to obtain the final ultrafiltration membrane.
[0028] Detection test 1. Contact angle test experiment: Take the ultrafiltration membranes prepared in Examples 1-3 and Comparative Examples 1-3, place them on the test bench of a water contact angle tester, drop 4 μL of water on the surface of the ultrafiltration membrane at room temperature, take photos to measure the angle between the cross section of the water drop and the membrane surface, test each ultrafiltration membrane 5 times at different water drop positions, calculate the average value, and record it in Table 1.
[0029] 2. Ultrafiltration membrane circulation experiment: The ultrafiltration membranes prepared in Examples 1-3 and Comparative Examples 1-3 were tested using a cross-flow filtration device: (1) Before the test, the ultrafiltration membrane was pre-pressed with pure water at 0.15 MPa for 30 min; (2) Adjust the pressure to 0.10 MPa, record the volume of pure water passing through every 10 minutes, and continue to record the superimposed volume for 1 hour; (3) Replace pure water with 0.1 g / L BAS solution and perform the same operation as above. Record the volume of BAS solution passing through every 10 min and continue to record the superimposed volume for 1 h. Then collect the filtrate and contaminated liquid and test their absorbance at 280 nm using a UV-visible spectrophotometer. (4) After flushing the front and back sides of the ultrafiltration membrane with pure water, continue working according to (2) for 1 hour and record the volume of pure water passing through; Calculate the flux of pure water and BAS solution J (L / m 2 h); The retention rate R (%) of the ultrafiltration membrane is calculated using the permeate concentration of BAS and the original solution concentration in (3); The recovery rate FRR (%) is calculated using the pure water flux in (2) and the pure water flux in (4); The irreversible pollution parameter R is calculated using the two pure water fluxes and the BAS flux. ir (%).
[0030] Table 1
[0031] Conclusion: From the above data, it can be seen that the ultrafiltration membrane prepared in Example 1 has good hydrophilicity and excellent anti-fouling performance; Comparative Example 1 does not perform polyethylene glycol blocking on Example 1, which has a significant effect on the hydrophilicity of the membrane, and the anti-fouling performance also decreases accordingly; Comparative Example 2 does not add sulfonated Ag-MOF, which slightly affects the hydrophilicity and anti-fouling performance; Comparative Example 3 does not add quaternized CNC, which obviously affects the anti-fouling performance of the ultrafiltration membrane. It can be seen that quaternized CNC effectively improves the anti-fouling performance of the ultrafiltration membrane.
[0032] Finally, it should be noted that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for preparing an ultrafiltration membrane for deep water treatment, characterized in that: The following steps are involved: Step 1: After drying and removing water from phenolphthalein, 4,4'-dichlorodiphenyl sulfone, anhydrous potassium carbonate and polyethylene glycol respectively, phenolphthalein, 4,4'-dichlorodiphenyl sulfone and anhydrous potassium carbonate are mixed, toluene and dimethylacetamide are added, and the mixture is heated to 140° C. and stirred for reaction for 6-10 hours until no water is taken out, and the mixture is heated to 160-180° C. to remove toluene, and the mixture is continued to react for 8 hours, and the mixture is cooled to 150° C., polyethylene glycol is added, and the mixture is continued to react for 1-2 hours, and the mixture is poured into pure water for sedimentation, and dilute hydrochloric acid is added dropwise, and the solid is filtered out and then crushed, and then washed and dried to obtain segmented polysulfone particles; Step 2: Mix the segmented polysulfone particles prepared in step 1 with polyvinyl pyrrolidone, sulfonated Ag-MOF, quaternized cellulose nanocrystals, and N-methylpyrrolidone, stir at 40-60°C for 6-8h, and then vacuum degas for 1h to obtain a casting solution; pour the casting solution onto a clean glass plate, use a scraper with a gap of 100-150μm to scrape it into a flat membrane, let it stand for 15-30s, immerse it in pure water until the primary membrane falls off, replace the pure water every 6-8h to obtain the final ultrafiltration membrane.
2. The method for preparing an ultrafiltration membrane for deep water treatment according to claim 1, characterized in that: In step 2, the ultrafiltration membrane comprises the following raw materials in parts by weight: 15-20 parts of segmented polysulfone particles, 3-5 parts of polyvinyl pyrrolidone, 2-5 parts of sulfonated Ag-MOF, 6-10 parts of quaternized cellulose nanocrystals and 70-80 parts of N-methylpyrrolidone.
3. The method for preparing an ultrafiltration membrane for deep water treatment according to claim 1, characterized in that: In step 1, the usage ratio of phenolphthalein, 4,4'-dichlorodiphenyl sulfone and polyethylene glycol is 1 mol: 1 mol: 25-80 g.
4. The method for preparing an ultrafiltration membrane for deep water treatment according to claim 1, characterized in that: The preparation steps of sulfonated Ag-MOF are as follows: dopamine hydrochloride is placed in a Tris buffer solution with a pH of 8.5, Ag-MOF is added and ultrasonicated for 10 minutes, the reaction is stirred for 4-6 hours, centrifuged, washed and dried, then transferred to pure water and ultrasonicated for 20 minutes, sodium 3-mercapto-1-propane sulfonate is added, the temperature is raised to 50-60°C, the reaction is stirred for 24 hours, centrifuged, washed and dried.
5. The method for preparing an ultrafiltration membrane for deep water treatment according to claim 4, characterized in that: The mass ratio of Ag-MOF, dopamine hydrochloride and sodium 3-mercapto-1-propane sulfonate is 1:1:(0.6-1.5).
6. The method for preparing an ultrafiltration membrane for deep water treatment according to claim 1, characterized in that: The preparation steps of quaternized cellulose nanocrystals are as follows: Step s1: Take cellulose nanocrystals and place them in a nitric acid solution for oscillation activation for 6 hours, then freeze-dry them, mix them with sodium periodate, place them in pure water, stir and react for 3 hours, then add ethylene glycol, centrifuge and wash them with water, mix them with cysteine, heat them to 40°C under nitrogen protection and stir them for 5 hours to obtain thiolated cellulose nanocrystals for later use; Step s2: dissolving dimethylaminoethyl methacrylate in N,N'-dimethylformamide, adding dodecane bromide, stirring and reacting for 48 hours under a nitrogen atmosphere, adding anhydrous ether to repeat precipitation and purification to obtain a quaternary ammonium salt monomer for later use; Step s3: placing the thiolated cellulose nanocrystals prepared in step s1 in dimethyl sulfoxide, adding the quaternary ammonium salt monomer prepared in step s2 and 2,2-dihydroxymethylpropionic acid, introducing nitrogen, reacting under ultraviolet light for 10 hours, centrifugally washing and freeze-drying to obtain quaternary ammonium cellulose nanocrystals.
7. The method for preparing an ultrafiltration membrane for deep water treatment according to claim 6, characterized in that: In step s1, the mass ratio of cellulose nanocrystals to sodium periodate and cysteine is 1:(0.6-1):(1-2); in step s2, the volume ratio of dimethylaminoethyl methacrylate to dodecane bromide is (4-5):
6.
8. The method for preparing an ultrafiltration membrane for deep water treatment according to claim 6, characterized in that: In step s3, the mass ratio of the thiolated cellulose nanocrystals to the quaternary ammonium salt monomer is 1:1; the mass fraction of 2,2-dihydroxymethylpropionic acid is 1.5%-2% of the thiolated cellulose nanocrystals.
9. An ultrafiltration membrane for deep water treatment, characterized in that: The compound is prepared by the preparation method according to any one of claims 1 to 8.
Citation Information
Patent Citations
Preparation method of permanent hydrophilic type polysulfone ultrafiltration membrane
CN105032220A
Method for synthesizing ABA type polysulfone family block copolymers
CN105504299A
Sulfhydrylation cellulose nanocrystalline and preparation method thereof
CN107325192A
Polysulfone block copolymer with non-linear block structure as well as synthesis method and application of polysulfone block copolymer
CN117384385A
Antibacterial double-block functionalized polyvinylidene fluoride material, ultrafiltration membrane as well as preparation method and application of antibacterial double-block functionalized polyvinylidene fluoride material and ultrafiltration membrane
CN118184913A